2022
DOI: 10.1097/moo.0000000000000848
|View full text |Cite
|
Sign up to set email alerts
|

Impact of unilateral hearing loss in early development

Abstract: Purpose of reviewThe purpose of this review is to provide an update on current literature as it relates to the impact of unilateral hearing loss for the pediatric population. Recent findingsCurrent studies further corroborate past research findings which reveal the potential consequences of unilateral hearing loss on spatial hearing, language, and neurocognitive functioning. Deficits among children with unilateral hearing loss may parallel those seen in children with bilateral hearing loss, further challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Children with UCHL usually do not show much inconvenience in life than those with unilateral sensorineural hearing loss (SNHL), possibly because they still have two normal functioning cochleae and a normal bone conduction hearing pathway. Although children with UCHL tend to have better school performance than those with SNHL, most of them still report communication and behavioral problems and need some sort of resource assistance [ 51 , 52 ]. Recently, a neuroimaging study has revealed abnormally high brain activities in the left inferior temporal gyrus of UCHL patients, which is positively associated with the duration of hearing loss [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children with UCHL usually do not show much inconvenience in life than those with unilateral sensorineural hearing loss (SNHL), possibly because they still have two normal functioning cochleae and a normal bone conduction hearing pathway. Although children with UCHL tend to have better school performance than those with SNHL, most of them still report communication and behavioral problems and need some sort of resource assistance [ 51 , 52 ]. Recently, a neuroimaging study has revealed abnormally high brain activities in the left inferior temporal gyrus of UCHL patients, which is positively associated with the duration of hearing loss [ 53 ].…”
Section: Discussionmentioning
confidence: 99%